Contract administration model for the improvement of sanitation project management - Farfán Kehuarucho, Ulianov (2020)
The research work was carried out with the information and evaluation of executed contracts for the execution of works in the Sanitation Services Provider Entity (EPS TACNA SA) Period 2012 - 2018, this investigation has the purpose of design a contract management model to improve the project management in sanitation works in the EPS TACNA SA; During this period of execution of works by CONTRACT MODE we have been able to see an innumerable numbers of queries, contradictions, omissions, negligence; having to be acquitted by the Supervision or directly by the Project Consultant. This confusing project generates risks in the projects executed by EPS Tacna SA, which in many cases cause the investments to be affected by paralyzes, unjustified delays finally in arbitration and this implies that they do not maintain their investment cycle and therefore loss of entity. FIDIC (International Federation of Consulting Engineers) is an international organization of standards for engineering and consulting construction best known by the family of FIDIC contract templates. This is how the new changes in the updating of the basic norms in the Peruvian State, they make every use of international recognized administrative standards, either as a basis for proposal or the writing of the final document. It is necessary to find a contract administration model to improve the project management in sanitation works so we need to plant a standard contract model that can control and overcome these shortcomings when they are executed in the EPS TACNA S.A. This research will yield a contract administration model that helps to manage a sanitation project from the initial lidding stage; good pro, contract signature, execution and the project closine is also proposed a standard contract model normative OSCE whit International regulations and contracts FIDIC, what will serve as the basis of solving the main problem